Prognostic Validity of the American Joint Committee on Cancer Eighth Edition TNM Staging System for Surgically Treated and Well-Differentiated Pancreatic Neuroendocrine Tumors: A Comprehensive Analysis of 254 Consecutive Patients From a Large Chinese Institution. Issue 5 (May 2019) - Yang, Min; Zhang, Yi; Zeng, Lin; Ke, Neng-wen; Tan, Chun-lu; Tian, Bo-le; Xiang, Bo; Liu, Xu-bao
Abstract : Objectives: We aimed to validate the novel American Joint Committee on Cancer (AJCC) eighth edition staging manual for well-differentiated (G1/G2) pancreatic neuroendocrine tumors (pNETs). Methods: Data of eligible patients were retrospectively collected, grouped, and analyzed by applying the new AJCC system. Results: According to the AJCC eighth staging manual for pNETs, 93, 66, 53, and 42 patients had stage I, II, III, and IV disease, respectively, with estimated 5-year overall survival (OS) rates of 96.9%, 92.8%, 48.4%, and 16.8% ( P < 0.005), respectively. A total of 57, 28, 20, and 17 patients with G1 pNETs and 36, 38, 33, and 25 ones with G2 tumors were defined by the new AJCC system as having stage I, II, III, and IV disease, respectively. The estimated 5-year OS for stage I, II, III and IV disease was 100.0%, 97.1%, 52.5%, and 18.2%, respectively, for G1 pNETs ( P < 0.005) and 94.2%, 90.3%, 38.7%, and 12.7%, respectively, for G2 tumors ( P < 0.005). The novel AJCC classification, tumor grading, and radical resection were all prognostic predictors for OS in patients with pNETs. Conclusions: The new AJCC eighth staging system for well-differentiated pNETs was prognostic and might be adopted in clinical practice.